MODAL SOSIAL DALAM INDUSTRI RUMAH TANGGA KERUPUK SAGU DI DESA PINTU GOBANG KARI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Hafizul Khair; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Sago cracker enterprises is one of the business community engaged in household industries, sago crackers business developed very well, as seen from the growing number of stands and development of industrial enterprises in the district sago crackers Middle Kuantan District Kuantan Singingi. Home Crackers industry Sago, the perpetrator Home Industry or Industry Household necessary social capital, in the achievement of social capital are elements of social capital; Trust (Trust), Reciprocal (Reciprocal) and Social Interaction of these elements, the core concept of Social Capital emphasis on community togetherness to achieve the goal of improving the quality of life and constantly making changes and adjustments continuously so that this will become a social capital then can be used as a reference in the Home Industry Crackers Sago. In this case the role of businesses sago crackers are very important in the economic activity of the fence or sago crackers sellers in the market, and the role of social capital elements are very important in the economic activity of businesses sago crackers. Subyek surveyed this time is sago crackers home industry entrepreneurs in the village of Kari Gobang Doors, amounting to 4 people, and writers also involves 2 buyers and 2 sellers / receiver sago crackers on the market using triangulation metide. Data retrieval research conducted by interview, observation and documentation. Interviews were conducted is a structured interview where researchers first prepare interview guidelines.Keywords: Social Capital, Entrepreneur, Crackers Sago